A Comparison of Models for Analyzing Educational Policy Processes: Advantages and Disadvantages - Wedikkarage, Lakshman (University of Colombo, 2010)
The present theoretical paper aims to examine the pros and cons of different models which may be used to analyze educational policy processes. Educational policy generally refers to rules and practices which a particular country or state maintains in order to govern the education system in that country or state. Educational policy is a term which is used to refer to almost any analysis of changes, reforms or developments in education, whether these occur at the macro (national or supra-national), meso (middle) or micro (local) level, and irrespective of whether the focus is on contemporary or historical events or processes. Educational policy studies are concerned with the study of educational policy processes. They deal with the nature, causes, and effects of alternative public policies. Policy studies and the analyses associated with them, aim to empower humans to undertake more effective collective action to solve or reduce significant policy issues. In analyzing these policy processes, educational researchers use a variety of models in relation to the various policy processes under investigation. While some researchers use a single model in such analyses, others opt to employ more than one model in their analyses bringing in multiple interpretations of educational policy processes. Every model, irrespective of the policy process under review, has its own advantsges and disadvantages. Therefore, educational researchers need to pay attention to the strengths and weaknesses of relevent models. The present theoretical paper examines the vital aspects of a spectrum of models starting off with rationalist models through marxist models to models based on theories of globalization